Visual metaphors in medical knowledge representation - Tercedor Sánchez, Maribel; Casado Valenzuela, Alicia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
Understanding the role of mental images and embodiment in metaphorical thought is fundamental to the study of metaphor in science in general, and in medicine in particular. And analysing typologies of metaphorical images and their function is a key issue in assessing their success in disseminating knowledge, since knowledge construction depends on the interaction between verbal and visual information (Ketola, 2016). In this article, we describe the premises and methodological steps followed in analysing and describing visual metaphorical information in medical texts for lay audiences. We follow a data-driven approach in which images were extracted from the VariMed database, a multimodal terminographical tool for translation, linguistic research and knowledge dissemination. An experiment was carried out to explore how successfully metaphorical images used as illustrations for specific medical concepts were identified and understood. We conclude that metaphorical images were preferred over non-metaphorical illustrations for medical concepts, which may point to lay audiences’ familiarity with metaphorical multimodal references.